Genome‐wide regulatory deterioration impedes adaptive responses to stress in inbred populations of Drosophila melanogaster*. (25th May 2018) - Schou, Mads F.; Bechsgaard, Jesper; Muñoz, Joaquin; Kristensen, Torsten N.
Abstract: Inbreeding depression is often intensified under environmental stress (i.e., inbreeding–stress interaction). Although the fitness consequences of this phenomenon are well‐described, underlying mechanisms such as an increased expression of deleterious alleles under stress, or a lower capacity for adaptive responses to stress with inbreeding, have rarely been investigated. We investigated a fitness component (egg‐to‐adult viability) and gene‐expression patterns using RNA‐seq analyses in noninbred control lines and in inbred lines of Drosophila melanogaster exposed to benign temperature or heat stress. We find little support for an increase in the cumulative expression of deleterious alleles under stress. Instead, inbred individuals had a reduced ability to induce an adaptive gene regulatory stress response compared to controls. The decrease in egg‐to‐adult viability due to stress was most pronounced in the lines with the largest deviation in the adaptive stress response ( R 2 = 0.48). Thus, we find strong evidence for a lower capacity of inbred individuals to respond by gene regulation to stress and that this is the main driver of inbreeding‐stress interactions. In comparison, the altered gene expression due to inbreeding at benign temperature showed no correlation with fitness and was pronounced in genomic regions experiencing the highest increase in homozygosity.